THE DRYINIDAE OF ARGENTINA (HYMENOPTERA - CHRYSIDOIDEA) - Virla, Eduardo; Olmi, Massimo (Acta Entomológica Chilena, 2022)
A hundred sixteen species of Dryinidae are listed in Argentina. The subfamily Apodryininae Olmi, the genera Crovettia Olmi, Lonchodryinus Kieffer, Megadryinus Richards, Trichogonatopus Kieffer, Esagonatopus Olmi and Apodryinus Olmi, and the Gonatopus cubensis (Richards) group (formerly Acrodontochelys) and G. nigrithorax (Ogloblin) group (formerly Dicondylus) are quoted for the first time in Argentina. Dryinus striaticeps (Kieffer) and Trichogonatopus albomarginatus (Cameron) are new records for Paraguay and Trichogonatopus hispidus Olmi for Bolivia. Fifty six new records for Argentina and forty one new distribution records at provincial level are given. The relationships between the Argentinian dryinids and their hosts are summarized.